2020
DOI: 10.3389/fpsyg.2020.01936
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Subthreshold Depression Among Constipation-Predominant Irritable Bowel Syndrome Patients

Abstract: Patients suffering from irritable bowel syndrome (IBS) may have some form of affective disorders that may worsen their symptoms. Lack of screening among IBS patients is one of the reasons for depression unawareness among healthcare providers. The present study was conducted to evaluate the prevalence of depression among patients with constipation-predominant IBS (IBS-C). A total of 240 IBS patients who fulfilled Rome III criteria were enrolled. The psychiatric assessment was evaluated using the Center for Epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Clinical unipolar depression or major depression disorder is a common mental illness, affecting more than 300 million people worldwide [ 35 ]. Depression is a form of behavioral dysregulation caused by an interplay of many factors, such as the environment, gender, age, and comorbidity with other pre-existing illnesses, including IBS [ 36 , 37 ]. Patients with IBS often suffer from significantly higher levels of depression compared to healthy subjects [ 38 , 39 , 40 , 41 ] as well as individuals affected by inflammatory bowel disease (IBD) [ 42 ].…”
Section: Irritable Bowel Syndrome and Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical unipolar depression or major depression disorder is a common mental illness, affecting more than 300 million people worldwide [ 35 ]. Depression is a form of behavioral dysregulation caused by an interplay of many factors, such as the environment, gender, age, and comorbidity with other pre-existing illnesses, including IBS [ 36 , 37 ]. Patients with IBS often suffer from significantly higher levels of depression compared to healthy subjects [ 38 , 39 , 40 , 41 ] as well as individuals affected by inflammatory bowel disease (IBD) [ 42 ].…”
Section: Irritable Bowel Syndrome and Depressionmentioning
confidence: 99%
“…Further sub-analysis in which IBS subtypes were considered separately showed the highest depression among IBS-C patients [ 40 ]. More recently, our research team demonstrated that about 32.1% of the IBS-C patient population in Malaysia has sub-threshold or subclinical depression, which can be easily missed in clinical practice [ 37 ]. According to Bahrudin et al (2020), the consumption of cultured drinks (probiotics) containing prebiotics in the form of polydextrose can significantly improve bowel function in IBS-C patients [ 111 ].…”
Section: Therapeutic Intervention In Ibs: Roles Of Prebiotics Probiotics and Psychobioticsmentioning
confidence: 99%
“…Investigating whether individuals with StD could have deficits in visual functioning is necessary for several reasons. Firstly, the prevalence of StD is higher than that of MDD (Cuijpers et al, 2007; Cuijpers et al, 2013; Mokhtar et al, 2020; Vaccaro et al, 2017). For example, a meta‐analysis of 22 studies about StD and MDD showed that the pooled prevalence rate of StD and MDD were 0.17 and 0.10, respectively (Cuijpers et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Subthreshold mental disorders (SMDs) (that do not meet full diagnostic criteria for mental disorders) are attracting increased attention in scientific research because SMDs can be an important source of countless other diseases and poor quality of life and thus may also be a cause of IBS development [ [104] , [105] , [106] , [107] , [108] , [109] , [110] , [111] , [112] , [113] ]. SMDs are often undiagnosed, although the prevalence of SMDs is higher than that of diagnosed mental disorders [ 104 ]. Furthermore, SMDs include the same symptoms as diagnosed mental disorders, except that they differ in the number, duration, severity, and frequency of symptoms and exclusion criteria [ 107 ].…”
Section: Ibs: Comorbidity With Mental Diseases and Subthreshold Menta...mentioning
confidence: 99%